Province vs Colony: Two paradigms of cultural interaction - Lidin, Konstantin; Belobrykina, Olga (project baikal, 2021)
The article considers two paradigms of the center-periphery interaction in the mixed and multiethnic systems. The historical examples show the peculiarities of the colonial paradigm where the peripheral culture is suppressed and displaced by the culture of the center (metropolis). The eparchial paradigm is based on cross-cultural interaction and enrichment between the center and the provinces. Within the final decades of the 20th century, the eparchial principle was replaced by the “cultural colonization” on the global scale. As a result, the “global West” culture is degrading to its lowest terms, which has a negative impact on the sphere of education.
Keywords: social psychology; history; culture; imperialism; metropolis; colony; province; architecture